Parallel Insertion Endoscopic Technique for Precise Catheter Placement in Cystic Craniopharyngiomas - Mori, Ryosuke; Joki, Tatsuhiro; Nonaka, Yuichiro; Ikeuchi, Satoshi; Abe, Toshiaki (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background Total removal of craniopharyngioma is the most acceptable therapeutic modality; however, there are cases in which radical excision is not possible. To reduce the cystic component volume, an Ommaya reservoir catheter can be placed endoscopically. However, there are certain complications and risks with this type of maneuver, such as misplacement of the catheter, which may result in leakage of cyst contents or installed fluids such as bleomycin. Thus, accurate placement of intracystic catheter is extremely important.Patients and Methods The authors placed Ommaya reservoir catheters running over the outer surface of a transparent endoscopic sheath in three cases.Results This neuroendoscopic procedure permits easier manipulation of the catheter and precise placement of the catheter tip. This technique was useful for placement of Ommaya reservoir catheters.Conclusions This new technique of catheter placement with neuroendoscopy is more accurate, safer, and less invasive.
Keywords: craniopharyngioma; neuroendoscope; neuronavigation; Ommaya reservoir